2010
DOI: 10.1371/journal.pone.0013193
|View full text |Cite
|
Sign up to set email alerts
|

R-SNARE Homolog MoSec22 Is Required for Conidiogenesis, Cell Wall Integrity, and Pathogenesis of Magnaporthe oryzae

Abstract: Soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins mediate intracellular vesicle fusion, which is an essential cellular process of the eukaryotic cells. To investigate the role of SNARE proteins in the rice blast fungus Magnaporthe oryzae, MoSec22, an ortholog of Saccharomyces cerevisiae SNARE protein Sec22, was identified and the MoSEC22 gene disrupted. MoSec22 restored a S. cerevisiae sec22 mutant in resistance to cell wall perturbing agents, and the ΔMosec22 mutant also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
98
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 71 publications
7
98
0
Order By: Relevance
“…The aim was to analyze whether chitinase expression patterns are altered during cell wall stress. T. virens was found to be very sensitive to Congo red and calcofluor white, and while for other fungi concentrations in the range of 50 to 200 g/ml of these substances are used (9,14,17), for T. virens, addition of more than 5 g/ml Congo red to the medium with the spore suspension in liquid, static cultures led to such a drastic decrease in growth that comparison with normal growth was not possible. Unfortunately, growth on calcofluor white was completely abolished even at 1 g/ml under these growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The aim was to analyze whether chitinase expression patterns are altered during cell wall stress. T. virens was found to be very sensitive to Congo red and calcofluor white, and while for other fungi concentrations in the range of 50 to 200 g/ml of these substances are used (9,14,17), for T. virens, addition of more than 5 g/ml Congo red to the medium with the spore suspension in liquid, static cultures led to such a drastic decrease in growth that comparison with normal growth was not possible. Unfortunately, growth on calcofluor white was completely abolished even at 1 g/ml under these growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the SEC22 ortholog of M. oryzae can restore defects in the yeast sec22 mutant (Song et al, 2010). Because Co-SEC22 exhibits striking sequence similarity to Mo-SEC22 (80% identity), it is plausible that M. oryzae SEC22 and C. orbiculare SEC22 are functional orthologs of the yeast SEC22 involved in transport between the ER and the Golgi apparatus (Jahn and Scheller, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…81 MoSec22 and MoVam7, the orthologs of yeast SNARE proteins Sec22 and Vam7, can also be demonstrated to have functions in vacuole assembly, which underlie the growth, conidiation, appressorium formation, and pathogenicity of M. oryzae. 82,83 Similarly, MoMon1 and MoYpt7 are the orthologs of the yeast proteins Mon1 and Ypt7.…”
Section: Molecular Mechanisms Of Autophagy In Pathogenic Fungimentioning
confidence: 99%